Li–CO2 Batteries: Bamboo‐Like Nitrogen‐Doped Carbon Nanotube Forests as Durable Metal‐Free Catalysts for Self‐Powered Flexible Li–CO2 Batteries (Adv. Mater. 39/2019). Issue 39 (23rd September 2019) - Li, Xuelian; Zhou, Jingwen; Zhang, Junxiang; Li, Matthew; Bi, Xuanxuan; Liu, Tongchao; He, Tao; Cheng, Jianli; Zhang, Fan; Li, Yongpeng; Mu, Xiaowei; Lu, Jun; et al.
Abstract : In article number1903852, Jianli Cheng, Jun Lu, Bin Wang, and co‐workers describe the fabrication of a fiber‐shaped self‐powered Li–CO2 battery based on bamboo‐like N‐doped carbon nanotube fibers working as the cathode for the Li–CO2 battery and the counter electrode for the dye‐sensitized solar cells simultaneously; they demonstrate high energy‐conversion efficiency, long cycle life, good stability, and flexibility.